Rhythm pattern discovery in Niger-Congo story-telling - Gibbon, Dafydd (Frontiers in Communication, 2023)
Description of interactive oral story-telling in West African Niger-Congo languages, 'orature' in contrast to 'literature', has traditionally been firmly in the domain of anthropological linguistics. However, the discourse structures of narrator-responder interaction and call-response song interludes and their prosody are an open challenge to discourse analysts, linguists and phoneticians who specialise in language interaction rather than language structures. A selection from the orature of different Niger-Congo languages of West Africa is analysed from the perspective of macrostructural discourse phonetics, with the focus on the automatic analysis and classification of rhythms based on long-term spectral information, but also related to sociolinguistic scenario categories. In this transdisciplinary methodology, long time domains are studied which differ greatly from the typical short time domains of under 10 s which are common in phonology and phonetics, and can range up to 10 minutes and beyond in a complete story. Using long-term spectra and spectrograms of both amplitude and frequency modulation of speech, long-distance timing regularities and their variation during story-telling exchanges are analysed in detail. The theoretical background is a further development of Speech Modulation Theory, Rhythm Formant Theory, which models rhythms as high magnitude peaks in the low frequency speech spectrum around 1~Hz. The data are taken from fieldwork materials collected in fieldwork projects in Côte d'Ivoire and Nigeria, and include both oral story-telling and the contrasting genre of reading aloud. The data are analysed using quantitative clustering methods and relations between rhythm patterns, styles and genres are uncovered. Finally, the results are summarised, the explanatory value of the approach is outlined, and the relevance of the results for practical applications is discussed.